A practicum at General Tuna Corporation, General Santos City, Philippines - Tocmo, Restituto Tajora (2007)
As part of the curriculum of the BS Food Technology, the student underwent a plant practice at General Tuna Corporation, in General Santos City, from April 17 to May 22, 2006. The 288-hour plant practice provided the student with adequate to the actual processing operation in the Export Division and other department of the company. The practicum was spent mainly in the production line where the trainee experienced hands-on training on the basic production and processing operations employed by the company and on the quality procedures implemented to ensure product quality and safety. During the practicum the student encountered minor problems in the existing operation as well as in the technical and human aspect of management of a Food Manufacturing Plant. This manuscript aims to document the information the student gathered from the plant practice and to suggest possible solutions to optimize existing processing operation of the company
Thesis (BS Food Technology) -- University of the Philippines Mindanao, 2007
Keywords: General Tuna Corporation; General Tuna Corporation -- General Santos City; Tuna; Tuna -- Canning; Tuna -- Thermal processing; Tuna -- Commercial sterilization; Retort pouch